Using Microsoft Excel 2010. - Jelen, Bill; Syrstad, Tracy (Que, 2010)
Using Microsoft Excel 2010 brings you over 45 media elements detailing everything from getting familiar with the Excel interface and accessing the Excel Web App to using SmartArt and creating macros. Watching this media is the fastest way to get comfortable with the newest version of Microsoft Excel. Topics covered include signing up for a Windows Live ID, converting formulas to values, using Format Painter, using conditional formatting, using Goal Seek to return a value, using the AutoSum feature, using the Quick Sort buttons, using the search function to filter for specific dates, linking SmartArt to cells, recording a macro using relative referencing, and much, much more!